Income and Trust Influences on ZIS Payment Interest: Evidence from Zakat Institutions in Palopo City - Cut Ade Tiara; H. Husmaruddin; Sri Wahyuni Mustafa (Manunggal Halim Jaya, 2026)
This study examines the influence of income and trust in zakat collection institutions on ZIS payment interest among Muslim communities in Palopo City, Indonesia. Zakat, infaq, and sedekah (ZIS) play a crucial role in promoting social welfare and economic redistribution, yet public participation in formal ZIS payments remains below its potential. Understanding behavioural factors influencing payment interest is therefore essential to improving institutional effectiveness. This research employs a quantitative approach using survey data collected from Muslim residents in Palopo City. Data were analysed using statistical techniques to examine the relationships between income, trust, and interest in paying ZIS through formal institutions. The findings indicate that trust in zakat management institutions plays a significant role in shaping individuals’ interest in paying ZIS, reflecting the importance of transparency, accountability, and institutional credibility. Income represents financial capacity and also contributes to payment interest, although its influence may vary depending on individual awareness and motivation. These results highlight that both economic and psychological factors are important in explaining ZIS payment behaviour. This study provides practical implications for zakat institutions to strengthen public trust through improved governance, service quality, and transparency. Enhancing these institutional aspects is expected to increase community participation and optimise ZIS collection for social welfare improvement.